2020
DOI: 10.1002/pan3.10116
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and seafood sustainability governance: Exploring the relationship between social capital and the performance of fishery improvement projects

Abstract: In the early 2000s, the sustainable seafood movement put forward the concept of fishery improvement projects (FIP), a structured multi‐stakeholder approach to address environmental challenges in a fishery and aims to use the power of the market to incentivize change. The intent of the FIP model is to allow fisheries that currently do not meet the MSC standard to maintain market access while working on credible improvements. As such, FIPs have become a widely promoted approach to sustainable fisheries and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Salas and Gaertner [ 17 ] also concluded that knowledge of the social, economic and behavioural dynamics of fishing is essential for effective fisheries management. Over the last few decades, the concept of sustainability has gained limelight in various fields and has been one of the extensively discussed aspects in the fisheries sector [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Likewise, Setthasakko [ 26 ] assessed key determinants that drive corporate sustainability and barriers that hinder its development by selecting two frozen seafood-processing companies as case studies.…”
Section: Literature Surveymentioning
confidence: 99%
“…Moreover, Salas and Gaertner [ 17 ] also concluded that knowledge of the social, economic and behavioural dynamics of fishing is essential for effective fisheries management. Over the last few decades, the concept of sustainability has gained limelight in various fields and has been one of the extensively discussed aspects in the fisheries sector [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Likewise, Setthasakko [ 26 ] assessed key determinants that drive corporate sustainability and barriers that hinder its development by selecting two frozen seafood-processing companies as case studies.…”
Section: Literature Surveymentioning
confidence: 99%
“…In addition, this study applied network analysis as a quantitative content analysis method for the visualization of human-nature relations. Social network analysis has been extensively utilized to examine the relationship between extracted factors and objects related to various types of social capital and natural resource governance (e.g., Barnes et al 2016;Bodin and Crona 2009;Crona and Bodin 2006;Cvitanovic et al 2017;Österblom et al 2017;Packer and Bailey 2020) in the context of environmental and sustainability sciences. However, the network analysis of text data has been utilized outside those disciplines, such as in medical, nursing, and educational applications, as one of the methods for content analysis (Danowski 1993;Osgood 1959).…”
Section: Objective Of This Studymentioning
confidence: 99%
“…The social capital theory drives on the relationship among networks to achieve access to resources which can take the form of information benefit not accessible to non-members of the network (Tian et al,2019;Packer et al,2020). Entrepreneur's internal network influences financial performance in the process of starting and integrating his business easily and successfully in gathering financial resources to start trading first (Stam et al, 2014;Sforzi and Bianchi, 2020), even outside suppliers may question how new companies' regulation are carried (Stinchcombe, 1965;Akintimehin et al, 2020).…”
Section: Social Capital and Firm Performancementioning
confidence: 99%